Social Justice Work in the University: Understanding Student and Staff Perceptions and Aspirations for Decolonising the Curriculum from a University-Wide Survey - Kyra Araneta; Kelsea Costin; Jennifer Fraser; Fatima Maatwk; Özge Süvari; Esra Tahir (Social Sciences)
In recent years, we have seen social movement-based calls for social justice and decolonisation in universities around the world. Some of these have been in response to specific events such as the murder of George Floyd in 2020, while others are rooted in longer standing social movements such as Rhodes Must Fall. These movements have served as catalysts for universities to rethink their commitments to social justice. This article presents the preliminary findings of a university-wide research initiative focused on understanding student and staff perceptions of decolonisation and their aspirations for decolonial work within a post-1992 institution in the United Kingdom. Positioned within the university’s broader commitments to anti-racism and as part of a student–staff partnership project focused on interrogating contemporary coloniality, this research investigates how participants understand and experience decolonial initiatives as well as the perceived impact of these efforts on curriculum, relationships, and institutional culture. By conducting a survey, we sought to unravel the complexities surrounding how students and staff conceptualise decolonisation, articulate their aspirations for decolonial initiatives, and envision the potential of student–staff partnerships as catalysts for transformative social justice work within the university. This study aims to enrich the discourse on social justice work in higher education by offering a critical lens on decolonial efforts and highlighting opportunities for collective action to rethink knowledge production and pedagogical practices. Grounded in the belief that decolonial research partnerships between students and staff are essential, the survey and article were developed by six researchers—three staff members and three students.